Psychoactive Effects of Lactobacillus johnsonii BS15 on Preventing Memory Dysfunction Induced by Acute Ethanol Exposure Through Modulating Intestinal Microenvironment and Improving Alcohol Metabolic Level - Sun, Ning; Zhu, Bin; Xin, Jinge; Li, Lianxin; Gan, Baoxing; Cao, Xi; Fang, Jing; Pan, Kangcheng; Jing, Bo; Zeng, Yan; Lv, Cheng; Zhao, Ling; et al. (Frontiers in Microbiology, 2022)
The negative influence of abuse ethanol (EtOH) on the body has been widely reported. Based on the microbiota-gut-brain axis hypothesis, this study aimed to demonstrate the potential psychobiotic role of Lactobacillus johnsonii BS15 underlying the preventive effects on the memory impairment induced by acute EtOH intake. Mice were randomly divided into three groups and administered with either phosphate buffered saline (PBS) (Control and Alcohol groups) or L.johnsonii BS15 (Probiotic group) throughout a 28-day experimental period. The results of 16S rRNA gene sequencing showed significant differences in ileal microbiota between the BS15-treated mice and control mice. Lactobacillus was the main targeting bacteria and significantly increased in BS15-treated mice, indicating the ability of BS15 to reconstruct the gut microbiota. Meanwhile, L. johnsonii BS15 significantly improved the level of intestinal tissue development prior to acute EtOH exposure, such as villus height, crypt depth and their ratio. Combined with the results of ileum microflora and villi development level, we found Lactobacillus, unidentified_Ruminococcaceae and Butyricicoccus with altered OTUs abundances also displayed positive associations with the villus height in ileum. Then acute EtOH exposure model was set up by gavage, which was given to the Alcohol and Probiotic groups in the day 28 of experiment. L. johnsonii BS15 effectively reduced the alcohol intoxication time blood alcohol concentration as well as the activities of ALT and AST in serum. Meanwhile, the improvement of alcohol tolerance time, the activities of ADH and ALDH in liver were showed by BS15 in acute alcohol-induced mice. We also found acute EtOH exposure reduced the exploration ratio in novel object recognition test, the escape latency and error numbers in passive avoidance test as well as the spontaneous exploration during the T-maze test in mice, which were significantly improved by the probiotic. L. johnsonii BS15 was found to significantly reversed the decreases of the antioxidant capacities (SOD, MDA and GSH) and mRNA expression of memory-related functional protein (BDNF and CREB) in hippocampal tissue after acute EtOH exposure. In conclusion, L. johnsonii BS15 intake appears as a promising psychoactive way to ameliorate alcohol-induced memory impairment through promoting metabolic level of EtOH.